Approach to Lower Urinary Tract Reconstruction: A Survey of Adult and Pediatric Urologist Perspectives and Experiences - Lembrikova, Katerina; Aninwene, George; Christensen, Katherine L.; Tandel, Megha; Kwan, Lorna; Gonzalez-Padilla, Daniel; Teoh, Jeremy; Sturm, Renea (Frontiers in Urology, 2022)
Introduction: Robotic adoption has rapidly increased within urology. Initial uptake in adult urology has outpaced that seen in pediatric procedures.(1, 2) The aim of this study was to determine adult and pediatric urologist satisfaction with specific procedural steps in LUTR using an open versus robotic approach and define drivers and barriers to robotics adoption to inform device development relevant to current needs. Methods: A survey was distributed to practicing urologists. Questions assessed surgeon demographics, technology adoption, satisfaction with anastomotic steps in continent neobladder (CN) and augmentation cystoplasty (AC), and drivers/barriers influencing robotic use. Results: Of 110 respondents, 49% practiced in academic institutions; 51% reported non-academic, private, or other. Specializations were pediatrics (36%), oncology/robotics (25%), or other (39%). 68% completed training in the past decade. In the past year, 55% completed only open CN or AC, 36% only robotic, and 9% both. Of those that performed robotic procedures, 5% used only an intra-corporeal approach, 85% used only extra-corporeal, and 10% used both. Surgeons who performed robotic LUTR alone expressed high satisfaction with all CN and AC anastomoses (bowel, bowel-bladder or bladder-bladder, ureteroenteric or urethrovesical). Overall, urologists found urethrovesical anastomoses more satisfactory via robotic approach. Pediatric urologists had the lowest satisfaction scores for the robotic approach in AC. In terms of robotic adoption, major drivers for CN were adoption by neighboring institutions, improved perioperative outcomes, and equivalent oncologic outcomes; barriers were cost of robotic purchase and maintenance, surgeon support for robotics, and difficult learning curve. Major drivers for AC were adoption by neighboring institutions, decreased operative time, and equivalent oncologic outcomes; barriers were increased operative time, cost, and minimal perceived benefit of extracorporeal procedures. Conclusion: Urologic oncologists and surgeons performing robotic LUTR alone were highly satisfied with the robotic approach. Pediatric urologists reported lower overall satisfaction with robotic steps in LUTR, potentially corresponding with limitations of current robotic platforms for pediatric application and relative training exposure. Major drivers overall were competition and outcomes; major barriers were cost, operative time, and learning curve. Maximizing surgeon experience through training and innovations to reduce complication rates will facilitate broader adoption of robotics in LUTR.